Impact of Covid-19 Pandemic on Unemployment in Indonesia - Sabran Sabran; Apridar Apridar; Muhammad Abrar (International Journal of Quantitative Research and Modeling, 2023)
The Covid-19 pandemic has had a significant impact on the economy. As a result, many companies were forced to close, and employees lost their jobs. Several economic variables suspected of mediating the impact of the Covid-19 pandemic on unemployment include investment, economic growth, and inflation. This study aims to determine the impact of the Covid-19 pandemic on unemployment in Indonesia either directly or through the mediation of investment, economic growth, and inflation. This research was conducted using panel data regression in 34 provinces in Indonesia in the 2018Q1 – 2021Q4 period. Through path analysis, the results showed that the Covid-19 pandemic has a direct positive impact on unemployment. The economic growth variable significantly mediates the effect of the Covid-19 pandemic on unemployment. Meanwhile, investment and inflation variables do not have a significant effect. This research is expected to provide an objective picture of the impact of the Covid-19 pandemic on unemployment in Indonesia and become a benchmark for policy formulation in dealing with the impact of this pandemic.